Robustness of Bifidobacterium longum LMG 13197 encapsulated in lyophilized Vegetal BM 297 ATO-inulin lipid-based synbiotic microparticles - Thantsha, Mapitsi Silvester (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.